EKSPLORASI FUNGI MIKORIZA ARBUSKULA PADA TINGKAT KELERENGAN LAHAN BERBEDA DI LAHAN KONSERVASI TANAMAN NANAS LOKAL - Sanjaya, Muhammad Fahyu; Arham, Ihsan; Sukmawati, Sri; Irlan; Kurniati; Burhan, Abd Rukman (Jurnal Tanah dan Sumberdaya Lahan, 2025)
This study aimed to explore the characteristics of Arbuscular Mycorrhizal Fungi (AMF) across varying land slope gradients in the conservation area of local pineapple plantations in Majene Regency. The analysis was conducted on five slope categories: flat (0-8%), gentle (8-15%), moderately steep (15-25%), steep (25-45%), and very steep (>45%), to examine the spore density and morphology of AMF as well as to see its relationship to ecological factors such as climate and topography. The results revealed that slope gradients significantly influenced AMF spore density, with the highest density observed on moderately steep and steep slopes. In contrast, lower densities were recorded on flat, gentle, and very steep slopes. Four AMF spore genera were identified: Glomus, Acaulospora, Gigaspora, and Scutellospora. Glomus was dominant across all slopes, Acaulospora was more prevalent on moderate slopes, and Gigaspora preferred steep slopes. Scutellospora was detected in limited quantities on extreme slopes. Environmental factors, including stable temperatures (27.61 °C-27.77 °C), high relative humidity (79.44%-80.41%), and varying precipitation levels, influenced AMF spore distribution and morphology. These findings emphasize the critical role of topography and climate in supporting AMF sustainability in management strategies to conserve AMF biodiversity and enhance crop productivity.